Fatal pulmonary embolism following splenectomy in a patient with Evan’s syndrome: case report and review of the literature - Varun Monga; Seth M. Maliske; Usha Perepu (Thrombosis Journal, 2017)
Abstract Background Evans syndrome (ES) is a rare disease characterized by simultaneous or sequential development of autoimmune hemolytic anemia (AIHA) and immune thrombocytopenia (ITP) with or without immune neutropenia. Splenectomy is one of the treatment options for disease refractory to medical therapy. Venous thromboembolism (VTE) following splenectomy for hematological diseases has an incidence of 10%. Case presentation Here we describe a case report of a young patient hospitalized with severe hemolytic anemia with Hgb 4.8 g/dl. He developed thrombocytopenia with platelet nadir of 52,000/mm3, thus formally diagnosed with ES. He failed standard medical therapy. He underwent splenectomy and had a fatal outcome. Autopsy confirmed the cause of death as pulmonary embolism (PE). Conclusions This case report and review of the literature highlight important aspects of the association between VTE, splenectomy, and hemolytic syndromes including the presence of thrombocytopenia. The burden of the disease is reviewed as well as various pathophysiologic mechanisms contributing to thromboembolic events in these patients and current perioperative prophylactic anticoagulation strategies. Despite an advancing body of literature increasing awareness of VTE following splenectomy, morbidity and mortality remains high. Identifying high risk individuals for thromboembolic complications from splenectomy remains a challenge. There are no consensus guidelines for proper perioperative and post-operative anti-coagulation. We encourage future research to determine which factors might be playing a role in increasing the risk for VTE in real time with hope of forming a consensus to guide management.